In situ ozone measurements within the 1987 Antarctic ozone hole from a high-altitude ER-2 aircraft - Proffitt, M. H.; Steinkamp, M. J.; Powell, J. A.; Mclaughlin, R. J.; Mills, O. A.; Schmeltekopf, A. L.; Thompson, T. L.; Tuck, A. F.; Tyler, T.; Chan, K. R. (1989)
In situ ozone measurements were made from the ER-2 aircraft during the 1987 Airborne Antarctic Ozone Experiment both inside and outside the ozone hole. Midday measurements from late August until late September during aircraft ascent near 53 deg S latitude indicate no clear temporal trend in ozone mixing ratio but instead reflect the distance of the measurement from the chemically perturbed region. The measurements made within the ozone hole at 72 deg S show altitude-dependent decreases in ozone of 61 percent at a potential temperature of 425 K down to 39 percent at 365 K. Temporal trends are also calculated at various positions relative to the boundary of the chemically perturbed region to locate the region of large ozone decreases and thereby accurately locate the boundary of the ozone hole.